The Representation of the Ordinary Heroine Evangelina In the Mass Media - Frisdahl, Sascha Maria (2019)
The following study uses the critical discourse analysis by Norman Fairclough as a method to analyze the representation of Evangelina Chamorro, who survived a mudslide in Peru in 2017. The purpose of this study is to investigate how the mass media represents an ordinary heroine in Peru by analyzing articles from the two national newspapers: Trome and La República. This analysis is performed by drawing a sample of six articles —three from Trome and three from La República—, which have been collected between the 16th of March 2017 and the 13th of May 2017.The theoretical framework of the study is ordinary heroism and the representation of women in the mass media. The study concludes that the four principal discourses in the representation of Evangelina is: survivor, woman, religious and poor. Both newspapers have the ability to create a heroic image around Evangelina using traditional values of gender of Latin American societies. Evangelina’s social identity is predominantly presented through her role as a mother, but the analysis further concludes that her identity as a mother is not fixed since it changes depending on the context.